2012
DOI: 10.1242/dev.078485
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling establishes the anterior border of the Ciona neural tube

Abstract: SUMMARYThe Ciona tadpole is constructed from simple, well-defined cell lineages governed by provisional gene networks that have been defined via extensive gene disruption assays. Here, we examine the patterning of the anterior neural plate, which produces placodal derivatives such as the adhesive palps and stomodeum, as well as the sensory vesicle (simple brain) of the Ciona tadpole. Evidence is presented that the doublesex-related gene DMRT is expressed throughout the anterior neural plate of neurulating embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 74 publications
4
120
0
Order By: Relevance
“…Bertrand et al, 2003;Davidson et al, 2006;Wagner and Levine, 2012). Our study demonstrates that FGF signaling also controls the timing of cell divisions and midline convergence of medial row I cells.…”
Section: Fgf/mapk Signaling and Cellular Morphogenesismentioning
confidence: 58%
See 1 more Smart Citation
“…Bertrand et al, 2003;Davidson et al, 2006;Wagner and Levine, 2012). Our study demonstrates that FGF signaling also controls the timing of cell divisions and midline convergence of medial row I cells.…”
Section: Fgf/mapk Signaling and Cellular Morphogenesismentioning
confidence: 58%
“…The Mnx −5 kb regulatory sequence was amplified from genomic DNA using the primers F-TATGGCGCGCCTCCTGATGTGACGGATTTATGACTG, R-TATG-CGGCCGCTAGCATCATTTTAAATCTTAAATATCAAAGGTTC and cloned into a H2B:Cherry-containing expression vector using NotI and AscI restriction sites. dnFGFR and Elk:VP64 were digested from Dmrt4> dnFGFR (Wagner and Levine, 2012) and Zicl>ElkLVP64 (Gainous et al, 2015) using NotI and BlpI and cloned downstream of the FoxB and Mnx enhancers. A clone of the Ciona MEK1/2 gene (citb42j03) was modified to produce the amino acid changes S116D and S220E using the primers TATGATCTTGTCCCTACAAACTCGTTGGCCATATCGTCGATCAGT-TGCCCGCTCAC and GTGAGCGGGCAACTGATCGACGATATGGC-CAACGAGTTTGTAGGGACAAGATCATA and the Stratagene quickchange site-directed mutagenesis procedure.…”
Section: Molecular Cloningmentioning
confidence: 99%
“…Previous work identified the FGF-MAPK signaling pathway as an important regulator of both specification and subsequent morphogenesis of the palps (Hudson et al, 2003;Wagner and Levine, 2012). Specifically, we showed that perturbation of FGF-MAPK signaling led to ectopic FoxC expression, but larvae that developed under these conditions failed to develop palps.…”
Section: Fgf-mapk Signaling Is Required For Proper Islet Patterningmentioning
confidence: 62%
“…6B, compare with control larva in Fig. 6A) (Wagner and Levine, 2012). Combining the DMRT>DN FGFR perturbation with FoxC>Islet, however, led to a rescue of palp development.…”
Section: Islet Rescues Palp Development Upon Inhibition Of Fgf Signalingmentioning
confidence: 79%
“…In Ciona intestinalis, several cases of differential ERK activation between sister cells have been described during marginal zone and neural lineage patterning. This differential ERK activation between sister cell pairs dictates their differential fate specification Stolfi et al, 2011;Wagner and Levine, 2012;Yasuo and Hudson, 2007) (reviewed by Lemaire, 2009). Importantly, in several of these cases, differential ERK activation is achieved via ephrin/Eph-dependent attenuation of FGF/ERK signalling (Picco et al, 2007;Shi and Levine, 2008;Stolfi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%